2017
DOI: 10.1002/lary.26800
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Eustachian tube dysfunction with balloon dilation: A systematic review

Abstract: Objective: Balloon dilation is a new entity in the therapeutic approach of Eustachian tube dysfunction. The aim of this systematic review is to evaluate the success of balloon dilation of the tuba auditiva in reducing symptoms in adult patients with Eustachian tube dysfunction.Data Sources: Embase, PubMed, and Cochrane Library. Review Methods: The systematic literature search was conducted independently by two authors based on title and abstracts, and resulted in 36 articles. These articles were screened as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 34 publications
0
100
0
4
Order By: Relevance
“…In comparison, the Bielefeld system inflates the balloon at 10 atm for 2 minutes whereas the Acclarent system does so at 12 atm for between 30 seconds and 2 minutes . Complications of balloon ET dilation such as pain, emphysema, bleeding and increased tinnitus have been reported to be mild and self‐limiting, and might be related to a higher pressure and larger diameter of the balloon. Although damage to the internal carotid artery would be of clinical importance due to its proximity to the ET, it has not been described previously in relation to a balloon catheter procedure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the Bielefeld system inflates the balloon at 10 atm for 2 minutes whereas the Acclarent system does so at 12 atm for between 30 seconds and 2 minutes . Complications of balloon ET dilation such as pain, emphysema, bleeding and increased tinnitus have been reported to be mild and self‐limiting, and might be related to a higher pressure and larger diameter of the balloon. Although damage to the internal carotid artery would be of clinical importance due to its proximity to the ET, it has not been described previously in relation to a balloon catheter procedure …”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of high‐pressure balloons have not been proved. In addition, complications such as subcutaneous emphysema and severe pain have been reported . Moreover, some authors reported that dilation of the bony canal should not be done because of risks of bony fracture and injury to the internal carotid artery .…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates that balloon size, inflation pressure and balloon insertion depth all impact on the changes induced in the ET during BET, and these are therefore likely to be important variables that determine the clinical effectiveness of the intervention. These technical details have typically been overlooked when comparing or combining BET clinical data, but they may underlie some of the variation seen in outcomes [2], and they will be important considerations during future development of the technique. Figure 4 demonstrates a significantly greater dissipation of energy during plastic deformation with the 6.0/6.5-mm balloons, a trend also seen in Fig.…”
Section: How Does the Choice Of Bet Balloon Device Or Technique Affecmentioning
confidence: 99%
“…Although clinical studies of BET have been of limited size and quality, BET appears to provide at least a short-term symptomatic improvement in patients with OETD [2]. Clinical data have also shown increased passive ET opening with Valsalva [12,15,16], a marked improvement in active ET opening with swallowing [17], and normalisation of tubomanometry R values [18,19].…”
Section: How Might Bet-induced Changes Improve Et Function In Cases Omentioning
confidence: 99%
See 1 more Smart Citation